2021
DOI: 10.1002/leg3.82
|View full text |Cite
|
Sign up to set email alerts
|

Potential health benefits of garden pea seeds and pods: A review

Abstract: Pea (Pisum sativum L.) is a nutritious pulse crop belonging to the leguminous family, and widely cultivated. In recent time, health and nutritional benefits of the pea and its by-products enriched with biomolecules, which have gained significant attention to the researchers and consumers. Peas are known for its pivotal nutritional value with high-quality proteins, dietary fibres, starch, carbohydrates and micronutrients including vitamins and minerals. It is also enriched with phytochemicals, antioxidants, fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 101 publications
0
35
1
Order By: Relevance
“…Recently, the pea (Pisum sativum), belonging to legumes, has received special attention, as it offers an opportunity to replace animal protein with a healthier, economically viable, and environmentally friendly source of protein. Pea seeds contain high amounts of essential amino acids and proteins, dietary fiber, minerals, vitamins, and phytochemicals that are related to their health beneficial properties [ 127 ]. Experimental studies have revealed that supplementation with fermented plant extract containing pea proteins might modulate gut microbiota and exert immunomodulatory effects [ 128 , 129 , 130 ].…”
Section: Evidence From Experimental and Clinical Studiesmentioning
confidence: 99%
“…Recently, the pea (Pisum sativum), belonging to legumes, has received special attention, as it offers an opportunity to replace animal protein with a healthier, economically viable, and environmentally friendly source of protein. Pea seeds contain high amounts of essential amino acids and proteins, dietary fiber, minerals, vitamins, and phytochemicals that are related to their health beneficial properties [ 127 ]. Experimental studies have revealed that supplementation with fermented plant extract containing pea proteins might modulate gut microbiota and exert immunomodulatory effects [ 128 , 129 , 130 ].…”
Section: Evidence From Experimental and Clinical Studiesmentioning
confidence: 99%
“…Incorporation of high amount of IDF in food model has increased product firmness during storage (Kurek & Wyrwisz, 2015). IDF in the food lowers transit time, as well as restricts the contact time of harmful substances with the intestinal walls (Kumari & Deka, 2021; Kurek & Wyrwisz, 2015). Various report suggested that the application of IDF in food processing industries use numerous emerging technologies to modify and enhance its physiochemical properties (Chen et al, 2013; Waliullah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…About 35% to 40% of solid waste GPP are generated during pea processing which represents a key issue in terms of environmental problems (Mateos‐Aparicio et al, 2010). Proximate analysis of GPP waste contains 26% cellulose, 20.5% hemicellulose, 3.92% lignin, 20.2% crude protein, and 5% ash (Kumari & Deka, 2021). There is very little insightful research conducted on dietary fiber of GPP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations